ROADMAP PENGEMBANGAN KOPI DI KAB. SOLOK SELATAN - Yulistriani Yulistriani; Yaherwandi Yaherwandi; Cindy Paloma (Jurnal Agrisep)
Coffee is an important commodity as a source of foreign exchange and regional income. Solok Selatan district the second largest coffee producer after Solok district in West Sumatra. But the potential for coffee development in Solok Selatan district  has not been clearly mapped before. Therefore this study aims is to analyze the potential for coffee development and construct a roadmap for coffee development in Solok Selatan district. This study uses primary and secondary data. For the first purpose, an in-depth interviews were conducted using the purposive sampling method and FGD (Focus Group Discussion) with coffee stakeholders, such as the coffee traders, farmers, agriculture counselor, the government and NGOs (Non-Governmental Organizations). The data, which is a results of interviews and FGDs are grouped into internal and external factors and then analyzed using the SWOT (Strengths-weaknesses-opportunities-threats) analysis to answer the second goal. The analysis results show that the Solok selatan district coffee commodity has potential to be developed because it have a unique flavor of lemon and casiavera. It is necessary to do several stages to develop of Solok Selatan coffee, namely product diversifications, build a coffee center outlets, and design an attractive coffee tourism areas. Thus, the existing potential is expected to develop optimally and Solok Selatan district can be known as one of the “coffee village” in West Sumatra.